Breadth and composition of polychaete diets and the importance of diatoms to species and trophic guilds - Checon, Helio Herminio; Pardo, Erica Veronica [UNESP]; Amaral, Antonia Cecilia Zacagnini (Springer Nature, 2017)
Polychaetes are important components of trophic webs in sandy beaches, mainly due to their abundance and diversity of feeding modes, acting as detritivores or primary/secondary consumers. We characterized diets of several polychaete species from intertidal sandy beaches by gut content evaluation. Diet breadth (Levins Index) was calculated for each species to evaluate the influence of different feeding strategies on this metric. Diatom composition was also assessed to verify the relevance of microphtyobenthic primary production to macrobenthic feeding on sandy beaches and its relationship with feeding strategies. A total of 2583 guts from 17 species were evaluated. Diet information is compared with literature, and added to taxa with previously unknown feeding habit. Diet breadths were generally low, but surface deposit feeders had the highest values. Scolelepis squamata guts were dominated by foraminfera, which may either be an specialization or local conditions. Subsurface deposit feeders usually had few items and lower breadths, highlighting the importance of organic matter to this guild. Diatoms were frequently found, and benthic were more frequently consumed than planktonic ones. The high numbers of benthic diatoms found for some species highlight the importance local food sources to sandy beach food webs.
Keywords: Diatoms; Feeding guild; Gut content; Polychaete feeding; Sandy beaches